A systematic review of the effect of mobile health on cardiac rehabilitation among coronary heart disease patients - Liu Hui; Xiao Xiao; Lu Chun-Mei; Ling Dong-Lan; Wei Rui-Hong (Sciendo, 2018)
Mobile health (mHealth) provides an innovative and effective approach to promote prevention and management of coronary heart disease. However, the magnitude of its effects is unclear. The aim of this systematic review was to examine the impact of mHealth-based cardiac rehabilitation outcomes among coronary heart disease patients.